Combining the methodologies of ethnography and grounded theory approach in understanding the characteristics of traditional knowledge related to medicinal plants of the batek in Kuala Koh,Gua Musang, Kelantan - Alias, Amran; Salleh, Hood; Mohamad Ismail, Shaharuddin; Abdul Ghani Aziz, Sarah Aziz; Salleh, Mohd Suhaidi; Kamri, Khairol Anuar; Mat, Bakri; Brahim, Sopian (Science Publishing Corporation (SPC), 2018)
Traditional knowledge related to medicinal plants of the indigenous people is a valuable asset to the community and could potentially bring economic returns to them if it is utilized appropriately. While much of the existing researches have been focused on documenting the knowledge, not much however, has been made known on the ‘holistic’ practice of the knowledge at the community level particularly in the Malaysian context. This is an important aspect as documenting the knowledge alone would not bring any meaning if the knowledge itself is not sustainably practiced by the communities who hold the knowledge. However, it is not an easy task to understand the management aspect of the knowledge especially if the researcher comes from a ‘different world view’ that the indigenous people themselves. This study is an attempt to combine two methodologies namely ethnographic approach as data gathering method and the principles of grounded theory approach as data analysis in understanding how the traditional knowledge related to medicinal plants is being protected by the indigenous people. Using the Orang Asli Batek in Kuala Koh, Gua Musang, Kelantan as a case study, this research involved multiple prolonged stays with the community (2013-2016) and employed ethnographic techniques of individual and group interviews, observation and participant observation as well as document analysis to gather the data. The collected data was analysed using the principles of grounded theory where all responses that were recorded in verbatim was organised and analysed in stages of coding such as ‘initial coding’, ‘selective coding’ and ‘theme’ which upon further analysis, had enabled the description of the characteristics of the traditional knowledge related to medicinal plants of the Bateks. The result of this study found that the combination of the two methodologies are indeed useful and in fact are complementary with each other in understanding the characteristics of the traditional knowledge related to medicinal plants of the Bateks of Kuala Koh as part of the indigenous community in the country. In particular, employing the two methods has enabled the study to identify the characteristics (forms) of the TK that can be found in an indigenous community such as the Bateks of Kuala Koh. This research has provided a greater understanding on the existing state of protecting the TK being practiced by the Bateks. The study also provides useful contribution to the body of knowledge as the methodological approach used could be employed by future researches in understanding similar approach in understanding similar phenomena.